NYCTEREUTES (MAMMALIA, CARNIVORA, CANIDAE) FROM LAYNA AND THE EURASIAN RACCOON-DOGS: AN UPDATED REVISION - SAVERIO BARTOLINI LUCENTI; LORENZO ROOK; JORGE MORALES (Rivista Italiana di Paleontologia e Stratigrafia, 2018)
The Early Pliocene site of Layna (MN15, ca 3.9 Ma) is renowned for its record of several mammalian taxa, among which the raccoon-dog Nyctereutes donnezani. Since the early description of this sample, new fossils of raccoon-dogs have been discovered, including a nearly complete cranium. The analysis and revision here proposed, with new diagnoses for the identified taxa, confirm the attribution of the majority of the material to the primitive taxon N. donnezani, enriching and clarifying our knowledge of the cranial and postcranial morphological variability of this species. Nevertheless, the analysis also reveals the presence in Layna of some specimens with strong morphological affinity to the derived N. megamastoides. The occurrence of such a derived taxon in a rather old site, has critical implications for the evolutionary history and dispersal pattern of these small canids. For instance, it reconciles the Western European and Asian records. Formerly, it was commonly thought that the evolutionary pattern of Early Pliocene raccoon-dogs in Europe was substantially different from the Asian one, where the advanced N. sinensis and the primitive N. tingi apparently coexisted in the same sites ; conversely, Europe was characterized by the occurrence of the single species N. donnezani. Our recognition of a derived taxon in the MN15 zone suggests the existence of similar ecological dynamics at the two extremes of the paleobiogeographic range of the genus (i.e., across the entire Eurasia).